2002
DOI: 10.1007/s00431-002-1053-2
|View full text |Cite
|
Sign up to set email alerts
|

The seroepidemiology of primary varicella-zoster virus infection in Flanders (Belgium)

Abstract: since varicella-zoster virus predominantly affects very small children and is generally perceived as benign, the required high coverage rate of a universal childhood varicella vaccination programme may be hard to attain. Adolescent strategies can minimise the population risks involved but the accuracy of non positive antecedents of chickenpox needs to be documented to assess the efficiency of such strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 27 publications
(38 reference statements)
4
29
1
Order By: Relevance
“…In 2007, 96.1% of Spanish women during their fertility period were immune to VZV (22). In Belgium, the prevalence of Anti-VZV IgG among young women was 100% (23). In addition to demographic, climatic, and socioeconomic factors, the performance of the varicella vaccination program in developed countries may partly explain the difference between these findings and our result.…”
Section: Discussioncontrasting
confidence: 74%
“…In 2007, 96.1% of Spanish women during their fertility period were immune to VZV (22). In Belgium, the prevalence of Anti-VZV IgG among young women was 100% (23). In addition to demographic, climatic, and socioeconomic factors, the performance of the varicella vaccination program in developed countries may partly explain the difference between these findings and our result.…”
Section: Discussioncontrasting
confidence: 74%
“…The observed age-specific seroprevalence is shown in the upper panel of Figure 1. Previous similar studies on VZV were reported by Thiry et al (2002) and Nardone et al (2007).…”
Section: Varicella Zoster Virussupporting
confidence: 82%
“…Negative predictive value of the history was 41% (Table 3), low and unreliable, as reported in the literature 30 . By contrast, positive predictive value of previous history of varicella in Xingu National Park was high, 98%, and it could be an efficient and economic measure to avoid vaccination, excluding from the "susceptible" category the individuals who referred previous varicella.…”
Section: Discussionsupporting
confidence: 57%
“…In these countries, indirect immunosorbent assay (ELISA) used to detect IgG VZV antibodies have demonstrated prevalence equal to or higher than 90% 1,9,16,21,27,[30][31] . In Brazil, general surveys have shown a seroprevalence of 85.4% 10 and 94.2% 26 , closer to the pattern observed in temperate countries.…”
Section: Introductionmentioning
confidence: 99%